Preparation method and application of active carbon fiber electrode material modified through nitrogen plasma chemical vapor deposition and acidification
Through chemical vapor deposition and acidification of nitrogen plasma, activated carbon fiber electrode materials are solved, and the problems of low efficiency and high cost of degradation of phenol polluted water in the prior art are achieved, and efficient and environmentally friendly hydrogen peroxide generation and phenol degradation effects are achieved.
Patent Information
- Application Number
- CN202411313897.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art has problems with low degradation efficiency, the need for exogenous oxidants and the generation of sedimented sludge when treating phenol-contaminated water. The traditional Fenton method is costly and it is difficult to continuously degrade organic pollutants.
Using nitrogen plasma chemical vapor deposition and acidification modified activated carbon fiber electrode materials, the modified activated carbon fiber electrode is formed through normal temperature nitrogen plasma chemical vapor deposition and nitric acid acidification treatment, which is used for electrochemical hydrogen peroxide production and catalytic degradation of organic pollutants. .
The hydrogen peroxide generation efficiency and phenol degradation performance are improved, and continuous degradation without the need for exogenous oxidants is achieved, cost is reduced, and treatment efficiency and stability are improved.
Smart Images

Figure CN119287652A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical hydrogen peroxide production for treating industrial wastewater, and specifically relates to a preparation method and application of an activated carbon fiber electrode material modified by nitrogen plasma chemical vapor deposition and acidification. Background Art
[0002] Phenol is considered a major pollutant of the environment and may cause water pollution. Its presence in water comes from two sources - natural phenomena and anthropogenic activities. Naturally occurring phenol originates from the decomposition of dead plants and animals in water; anthropogenic activities refer to the discharge of phenol from industries, agricultural sectors, households and municipalities. Whether in chemical production or in the petrochemical industry, phenol is often used as an intermediate in the production of chemicals such as alkylphenols, cresols and resins: phenolic resins are mainly provided by the construction industry, the wood industry and electrical appliances to meet various needs; dyes, textile industries and explosive materials require phenol as one of the raw materials, etc. The United States Environmental Protection Agency (USEPA) and Canada classify it as a priority pollutant through the National Pollutant Release Inventory (NPRI); at the same time, phenol is also classified as a hazardous substance, which can cause damage to human health, both acutely and chronically: long-term exposure may cause abnormal breathing, tremors, and then coma, and when the lethal dose estimated for humans based on body weight is reached, it may cause respiratory arrest.
[0003] Electro-Fenton technology mainly relies on metal ion catalysis to generate hydrogen peroxide and then produce hydroxyl radicals to achieve the purpose of oxidizing organic pollutants. Electro-Fenton technology is particularly good at degrading organic matter. It has shown good performance in both degradation rate and decontamination rate, overcoming the shortcomings of traditional Fenton, which produces a large amount of sedimentary sludge and requires continuous addition of hydrogen peroxide. The most important point that distinguishes the electro-Fenton reaction system from other water treatment processes based on Fenton reactions is that the electro-Fenton reaction can electrolyze to produce hydrogen peroxide, avoiding the cost and risk of producing hydrogen peroxide. In addition, divalent iron ions are continuously regenerated during the cathode reduction process, ensuring the continuity of degradation. From many aspects, electro-Fenton technology has broad application prospects in the field of environmental electrochemistry.
[0004] Activated carbon fibers have remarkable properties such as excellent volumetric capacity, high packing density, high specific surface area and uniform micropore volume, excellent adsorption capacity, fast adsorption / desorption rates, enhanced design flexibility and easy regeneration. ACFs have attracted a lot of attention in recent years due to these properties and their potential applications in a large number of small and large industrial applications. Their improved and tunable microporosity and fine porosity have led to their application in major research areas, namely natural gas storage, adsorbents in heavy metal industries, treatment and purification of water and air, hydrogen storage as a fuel, and electrochemical applications such as supercapacitors.
[0005] Plasma is the fourth state of matter in which both neutral and charged species exist, and has great potential for modifying carbon-based materials. Plasma treatment technology is a promising approach to improve the physicochemical properties of activated carbon fibers compared to other modification techniques, as the bond breaking by high-energy electrons and free radicals can more easily introduce chemically active surface species with less damage, resulting in superior surface properties. The plasma process can modify the surface properties of activated carbon fibers through different behaviors, such as penetration of high-energy gases to a depth of a few nanometers, rupture of covalent bonds, ion impact, etc. The activated surface can easily react with other excited gases to form functional groups. The functional groups modify the surface chemistry of activated carbon fibers to obtain customized properties, such as wettability, adhesion, wear or abrasion resistance, good friction characteristics, electrical properties, etc. Summary of the invention
[0006] In view of the above-mentioned technical problems existing in the prior art, the purpose of the present application is to provide a method for preparing an activated carbon fiber electrode material by nitrogen plasma chemical vapor deposition and acidification modification and its application.
[0007] The technical solution adopted by the present invention is as follows:
[0008] A method for preparing an activated carbon fiber electrode material by nitrogen plasma chemical vapor deposition and acidification modification, comprising: using sheet-like activated carbon fibers (the basic activated carbon fibers are from Jiangsu Sutong Carbon Fiber Co., Ltd., with a specific surface area of 1200 m 2 / g or so) is cleaned and pretreated, and the pretreated activated carbon fiber is subjected to room temperature nitrogen plasma chemical vapor deposition to obtain the first modified precursor activated carbon fiber N-ACF. The N-ACF is immersed in nitric acid and heated for acidification to obtain the second modified activated carbon fiber N-Acid-ACF, and the preparation is completed.
[0009] Furthermore, the cleaning pretreatment process includes: ultrasonically impregnating the activated carbon fiber with anhydrous ethanol and deionized water for 2-3 times respectively, the ultrasonic time is 20-60 minutes, and then drying.
[0010] Furthermore, the operation of room temperature nitrogen plasma chemical vapor deposition is carried out in a plasma chemical vapor deposition generator, and the nitrogen introduced therein is excited to generate highly excited N* plasma to bombard the activated carbon fibers and deposit defects. The RF power input power of the plasma chemical vapor deposition generator is 200-400W, the RF frequency is 10-15MHz, and the nitrogen gas intake volume is 50-200sccm.
[0011] Furthermore, the time for nitrogen plasma chemical vapor deposition of the activated carbon fiber is 5-20 minutes per side (after deposition on one side, the same operation is repeated to deposit on the other side), and nitrogen is continuously passed for 10-15 minutes after deposition.
[0012] Furthermore, the mass concentration of nitric acid is 20-40%, preferably 30%, the temperature of the heating acidification treatment is 70-90° C., preferably 75-80° C., and the treatment time is 0.5-2 h, preferably 0.8-1 h.
[0013] Furthermore, the material after the heating and acidification treatment is rinsed with deionized water for multiple times until the pH of the rinse solution is neutral.
[0014] The invention also discloses the application of the activated carbon fiber electrode material in electrochemical production of hydrogen peroxide or electrochemical catalytic degradation of organic pollutants.
[0015] Furthermore, the application method of the electrochemical production of hydrogen peroxide includes: using a 0.01-0.1M sodium sulfate aqueous solution as an electrolyte, adjusting the pH of the electrolyte to 2-4, using the activated carbon fiber electrode material as a cathode electrode, and a platinum sheet as an anode electrode, and performing an electrolytic reaction to produce hydrogen peroxide at a constant voltage of 5-20V.
[0016] Furthermore, the application method of electrochemical catalytic degradation of organic pollutants comprises:
[0017] Organic pollutants are added into an electrolyte containing 0.01-0.1M NaSO4 and 0.01-0.1mM Fe(Ⅱ), and the pH of the electrolyte is adjusted to 2-4. The activated carbon fiber electrode material is used as a cathode electrode and a platinum sheet is used as an anode electrode to electrocatalyze and degrade the organic pollutants at a constant voltage of 5-20V. The organic pollutants include phenol.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention gives full play to the characteristics of large specific surface area of activated carbon fiber, has the advantages of high treatment efficiency and green environmental protection, and can generate economic and social benefits in the field of industrial printing and dyeing wastewater and groundwater treatment;
[0020] 2. The reagents and electrode materials used in the present invention are cheap and easy to obtain. The hydrogen peroxide consumed in the electrolysis process is automatically regenerated under the condition of air ventilation, which ensures the continuous degradation of pollutants. Compared with the traditional Fenton method, no exogenous oxidant needs to be added;
[0021] 3. The nitrogen plasma process of the present invention can change the surface properties of activated carbon fibers through different behaviors, such as high-energy gas penetration to a depth of several nanometers, rupture of covalent bonds, ion impact, etc. The activated surface can easily react with other excited gases to form functional groups, thereby more efficiently changing the surface chemical properties of activated carbon fibers. In the preparation process of the electrode material of the present invention, the two synergistic modification processes can not only increase a large number of physical vacancies, but also provide more adsorption sites for the electronic transition state HOO* through nitrogen doping as chemical vacancies, effectively improving the electrical generation efficiency of hydrogen peroxide, while having ultra-high degradation performance for phenol and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The electron microscope scanning images of ACF, N-ACF, Acid-ACF and N-Acid-ACF obtained in Example 1;
[0023] Figure 2 are the Raman images of ACF, N-ACF, Acid-ACF and N-Acid-ACF obtained in Example 1;
[0024] Figure 3 It is a graph of hydrogen peroxide production of ACF, N-ACF, Acid-ACF and N-Acid-ACF obtained in Example 2;
[0025] Figure 4 : Phenol degradation diagram of ACF, N-ACF, Acid-ACF and N-Acid-ACF obtained in Example 3;
[0026] Figure 5 : TOC diagram of phenol waste liquid of ACF, N-ACF, Acid-ACF and N-Acid-ACF obtained in Example 4. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0028] In the embodiment of the present invention, the basic activated carbon fiber is sourced from Jiangsu Sutong Carbon Fiber Co., Ltd., with a specific surface area of 1200m 2 / g or so.
[0029] Example 1
[0030] The preparation method of the modified activated carbon fiber electrode material N-Acid-ACF comprises the following steps:
[0031] Step A: The activated carbon fiber is soaked in anhydrous ethanol and deionized water for three times for 30 minutes, and then dried in a 60°C oven to obtain the pretreated clean activated carbon fiber ACF. The electron microscope scanning image of the pretreated clean activated carbon fiber ACF is as follows: Figure 1 (a)
[0032] Step B: After obtaining the pretreated activated carbon fiber, a thin layer of sizing agent is applied on the surface to prevent it from absorbing moisture and dust in the air and to ensure the cleanliness of the carbon fiber surface.
[0033] Step C: Before use, the carbon fiber was oxidized and baked by hot air at 400°C for 30 minutes to remove the sizing agent to obtain pretreated activated carbon fiber ACF.
[0034] Step D: The activated carbon fiber pretreated in step C is subjected to room temperature nitrogen plasma chemical vapor deposition using a plasma chemical vapor deposition generator. Atomized liquid nitrogen is introduced into the plasma chemical vapor deposition generator. After the nitrogen gas is stably circulated, the radio frequency power supply of the plasma chemical vapor deposition generator is turned on to energize the nitrogen gas into a highly excited N* plasma. The activated carbon fiber is bombarded and defect-deposited by the high-energy N* plasma. The radio frequency power supply input power of the plasma chemical vapor deposition generator is 300W, the radio frequency frequency is 13.56MHz, the nitrogen gas intake volume is 100sccm, and the time required for nitrogen plasma chemical vapor deposition is 10 minutes per side (after one side is deposited, the same operation is repeated to deposit the other side again). After the deposition is completed, 100sccm of nitrogen gas must be continuously passed for 10-15 minutes. After the room temperature nitrogen plasma chemical vapor deposition operation is completed, the first modified precursor activated carbon fiber N-ACF is obtained. The electron microscope scanning image of N-ACF is shown in Figure 1 (b)
[0035] Step E: The pretreated activated carbon fiber ACF and N-ACF are treated with nitric acid respectively. The specific operation is: nitric acid with a mass concentration of 30% is heated in an 80°C water bath, the nitric acid is stirred, and then the ACF or N-ACF is immersed in the nitric acid. After the treatment time is 60 minutes, the ACF or N-ACF is taken out and rinsed with deionized water several times until the pH of the leaching solution is 7, and then the obtained electrode material is placed in a 60°C oven for drying. According to the operating method of step E, the acid-modified activated carbon fiber Acid-ACF and the secondary modified activated carbon fiber N-Acid-ACF are obtained respectively.
[0036] The electron microscope scanning images of Acid-ACF and N-Acid-ACF are shown in Figure 2. Figure 1 As shown in (c) and (d).
[0037] The electron microscope scanning images of the obtained ACF, N-ACF, Acid-ACF and N-Acid-ACF are shown in Figure 1 As shown, it can be observed that the surface of the untreated activated carbon fiber is smooth and complete; after nitrogen plasma chemical vapor deposition treatment, fine particles appear on the surface; the activated carbon fiber after acidification has various defects; and the surface of N-Acid-ACF appears to be rougher and has obvious bumps and undulations.
[0038] The Raman images of ACF, N-ACF, Acid-ACF and N-Acid-ACF obtained are as follows: Figure 2 As shown, it can be seen that both nitrogen plasma chemical vapor deposition treatment and acidification treatment can make the surface defects of activated carbon fiber more, and under nitrogen plasma chemical vapor deposition treatment, the D peak and G peak of activated carbon fiber are higher, and the CC bond stretching is obvious. N-Acid-ACF has the most defects and the most obvious stretching.
[0039] Combination Figure 1 , Figure 2 It can be concluded that the vacancies of activated carbon fibers increased after treatment, and the N* plasma chemical vacancies increased, which is more conducive to the generation of hydrogen peroxide and promotes the 2e - ORR reaction proceeds.
[0040] Comparative Example 1:
[0041] The preparation of the modified activated carbon fiber electrode material Acid-N-ACF, firstly prepare the pretreated activated carbon fiber ACF according to steps AC of Example 1, then perform nitric acid acidification treatment on the pretreated activated carbon fiber ACF according to step E of Example 1 to obtain acid-modified activated carbon fiber Acid-ACF. Finally, perform room temperature nitrogen plasma chemical vapor deposition operation on Acid-ACF according to step D of Example 1 to prepare the modified activated carbon fiber electrode material Acid-N-ACF.
[0042] Example 2
[0043] The ACF, N-ACF, Acid-ACF and N-Acid-ACF prepared in Example 1, or the modified activated carbon fiber electrode material Acid-N-ACF of Comparative Example 1, are applied to the electro-Fenton hydrogen peroxide production reaction, comprising the following steps:
[0044] A 250 ml container was placed in a 25°C constant temperature water bath, wherein the solution volume was 200 ml, the NaSO4 concentration was 0.05 M, and the pH was adjusted to 3. The cathode electrode was ACF, N-ACF, Acid-ACF or N-Acid-ACF prepared in Example 1 (the size of the electrode material was 2 cm×2 cm), the anode electrode was a platinum sheet, the reaction constant voltage was 15 V, and the initial pH was 3. The reaction time is 120 min, and samples are taken at time points of 0, 10, 20, 30, 60, 90, and 120 min, respectively. The method for detecting hydrogen peroxide is as follows: add 2 ml of the test solution into a 10 ml colorimetric tube, add 1 ml of 3 mol / L sulfuric acid solution and 2 ml of 0.05 mol / L potassium titanium oxalate solution into the colorimetric tube respectively, dilute to the scale line with deionized water, shake well and place for 10 min, measure the absorbance at a wavelength of 400 nm with the reagent blank as a reference, and calculate the hydrogen peroxide concentration of the sample solution according to the measured standard curve.
[0045] When the ACF, N-ACF, Acid-ACF and N-Acid-ACF of Example 1 or the modified activated carbon fiber electrode material Acid-N-ACF of Comparative Example 1 are used as cathode electrodes for electrolysis, the hydrogen peroxide production is shown in the figure below: Figure 3 As shown, it can be obtained from Figure 3 It can be seen that the production of hydrogen peroxide in the modified ACF at 120 minutes increased significantly, among which N-Acid-ACF was the most efficient in producing hydrogen peroxide as the cathode electrode.
[0046] In addition, by Figure 3 It can be seen that when the modification methods are exchanged in order, the hydrogen peroxide generation effect presented by the Acid-N-ACF electrode sheet as the cathode electrode is not good. This may be because the deposition of N* plasma fills the vacancies generated in the previous step, resulting in very few additional vacancies on the activated carbon fiber.
[0047] Example 3
[0048] The ACF, N-ACF, Acid-ACF and N-Acid-ACF prepared in Example 1 are applied to the catalytic oxidation electro-Fenton removal reaction of phenol-containing wastewater, which comprises the following steps:
[0049] A 250 ml container was placed in a 25°C constant temperature water tank, wherein the solution volume was 200 ml, the NaSO4 concentration was 0.05 M, the pollutant phenol concentration was 20 ppm, the FeSO4 concentration was 0.5 mM, and the pH was adjusted to 3. The cathode electrode was ACF, N-ACF, Acid-ACF or N-Acid-ACF (the electrode material size was 2 cm×2 cm) prepared in Example 1, and the anode electrode was a platinum sheet. The reaction constant voltage was 15 V, and the initial pH was 3. During the electro-Fenton catalytic reaction, 1 ml of the sample to be tested was taken at reaction times of 0, 5, 15, 30, 60, and 120 min, and 0.5 ml of methanol was added for quenching, and then the concentration of phenol was measured by liquid phase, and the removal rate of phenol in water by different catalytic materials was calculated.
[0050] When ACF, N-ACF, Acid-ACF and N-Acid-ACF were used as cathode electrodes for electrolysis, the phenol removal diagram was shown in Figure 2. Figure 4 As shown, it can be seen that compared with the unmodified ACF, the modified N-ACF, Acid-ACF and N-Acid-ACF have better removal effects on phenol, among which N-Acid-ACF as the cathode electrode has the most significant phenol removal effect.
[0051] Example 4
[0052] The ACF, N-ACF, Acid-ACF and N-Acid-ACF prepared in Example 1 are applied to the catalytic oxidation electro-Fenton degradation reaction of phenol-containing wastewater, which comprises the following steps:
[0053] The specific steps are basically the same as those in Example 3, with the only difference being that the reaction time of the solution is 360 min, and during the electro-Fenton catalytic reaction, 8 ml of the sample to be tested is taken at reaction times of 0, 60, 120, 180, 240, 300, and 360 min, respectively, and then the TOC in the solution is measured using a TOC analyzer, and then the degradation rate of TOC of the phenol solution in the water body by different catalytic materials is calculated.
[0054] When ACF, N-ACF, Acid-ACF and N-Acid-ACF are used as cathode electrodes for electrolysis, the TOC graph of phenol wastewater is as follows: Figure 5 As shown, it can be seen that compared with the unmodified ACF, the modified N-ACF, Acid-ACF and N-Acid-ACF have better and more thorough degradation effects on phenol degradation. Among them, the phenol removal degradation effect of N-Acid-ACF as the cathode electrode is the most outstanding.
[0055] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for preparing an activated carbon fiber electrode material by nitrogen plasma chemical vapor deposition and acidification modification, characterized in that After cleaning and pretreatment with sheet-like activated carbon fibers, the pretreated activated carbon fibers are subjected to room temperature nitrogen plasma chemical vapor deposition to obtain the first modified precursor activated carbon fibers N-ACF, and the N-ACF is immersed in nitric acid and heated for acidification to obtain the second modified activated carbon fibers N-Acid-ACF, and the preparation is completed.
2. The method for preparing an activated carbon fiber electrode material by nitrogen plasma chemical vapor deposition and acidification modification according to claim 1, characterized in that The cleaning pretreatment process includes: using anhydrous ethanol and deionized water to soak the activated carbon fiber for 2-3 times respectively, the ultrasonic time is 20-60 minutes, and then drying.
3. The method for preparing an activated carbon fiber electrode material by nitrogen plasma chemical vapor deposition and acidification modification according to claim 1, characterized in that The operation of nitrogen plasma chemical vapor deposition at room temperature is carried out in a plasma chemical vapor deposition generator, in which the nitrogen introduced is excited to generate highly excited N* plasma to bombard the activated carbon fibers and deposit defects. The RF power input power of the plasma chemical vapor deposition generator is 200-400W, the RF frequency is 10-15MHz, and the nitrogen gas intake volume is 50-200sccm.
4. The method for preparing an activated carbon fiber electrode material by nitrogen plasma chemical vapor deposition and acidification modification according to claim 1, characterized in that The time for nitrogen plasma chemical vapor deposition of activated carbon fiber is 5-20 minutes per side. After deposition on one side, the same operation is repeated to deposit the other side. After deposition, nitrogen is continuously passed for 10-15 minutes.
5. The method for preparing an activated carbon fiber electrode material by nitrogen plasma chemical vapor deposition and acidification modification as claimed in claim 1, characterized in that The mass concentration of nitric acid is 20-40%, preferably 30%, the temperature of heating acidification treatment is 70-90° C., preferably 75-80° C., and the treatment time is 0.5-2 h, preferably 0.8-1 h.
6. The method for preparing an activated carbon fiber electrode material by nitrogen plasma chemical vapor deposition and acidification modification according to claim 1, characterized in that The material after heating and acidification treatment is rinsed with deionized water several times until the pH of the eluent is neutral.
7. An activated carbon fiber electrode material prepared by the method according to any one of claims 1 to 6.
8. Use of the activated carbon fiber electrode material as claimed in claim 7 in electrochemical production of hydrogen peroxide or electrochemical catalytic degradation of organic pollutants.
9. The use according to claim 8, characterized in that The application method of the electrochemical production of hydrogen peroxide includes: using a sodium sulfate aqueous solution with a concentration of 0.01-0.1M as an electrolyte, adjusting the pH of the electrolyte to 2-4, using the activated carbon fiber electrode material as a cathode electrode and a platinum sheet as an anode electrode, and performing an electrolytic reaction to produce hydrogen peroxide at a constant voltage of 5-20V.
10. The use according to claim 8, characterized in that The application method of electrochemical catalytic degradation of organic pollutants includes: adding organic pollutants to an electrolyte containing 0.01-0.1M NaSO4 and 0.01-0.1mM Fe(II), adjusting the pH of the electrolyte to 2-4, using the activated carbon fiber electrode material as a cathode electrode and a platinum sheet as an anode electrode, and performing an electrolytic catalytic degradation reaction of the organic pollutants at a constant voltage of 5-20V; wherein the organic pollutants include phenol.
Citation Information
Cited By
Plasma modified biochar electrode and preparation method and application thereof
CN120157229A
Plasma modified biochar electrode and preparation method and application thereof
CN120157229B